Change and Mechanism of Place Identity of Residents in Enterprise Community: A Case Study on Community of Northwest First Printing and Dyeing Factory, Xi'an - Huang Kun; Wu Wenheng; Yang Bihong; Shi Haijin (Redai dili, 2022)
"Place identity" is an important concept that measures personal place emotion and reflects the complicated dynamic relationship between personal identity and one's local environment. Enterprise communities (ECs) are a major type of gated, walled-off residential spaces. They were built and managed mostly by the state or collectively owned enterprises during the planning economy period, and many are still employed in urban China. Understanding the place identity of EC residents is of great significance for community renewal, neighborhood revitalization, and sustainable urban development. Using the Northwestern First Printing and Dyeing Factory community as a typical example, this paper uncovers the changes and mechanisms of personal place identity under the influence of social environment changes and community transformation using grounded theory, while discussing its policy implications. The main results are as follows: first, 13 open coding items, such as cognitive change of identity, reduced familiarity, weakened social interaction, and dilapidated housing construction were defined; further, four axial codings, including personal identity changes, emotional memory changes, identity change in social life, and physical environment identity, were set, and an analysis framework on the change of residents' place identity in the ECs (selective coding) was built. Second, the residents' personal awareness in ECs has changed from Danwei people in the era of planned economy to social people in the market economy period and to left-behind elderly groups in the future. Third, inherited collective memory maintains the residents' positive place identity. Alienation of social interaction and socialization of community management weaken place identity. The dilapidated material environment and backward support facilities cause the residents to experience negative identity. Fourth, residents build their own and local identity in the interaction between the EC environment and society that accompanies their life and growth, and the identity changes along with the variation of external social environment and internal individual characteristics. External factors such as state-owned enterprise reform and housing policies have led to enterprise transitions and changes in social space in the ECs, affecting residents' emotional experience and identity. Internal factors such as length of residence, individual characteristics, psychological factors, and individual experiences all have an effect on identity. These jointly shape the residents' place identity and can alter its processes. Finally, this work is helpful in providing insight into socialist work-unit communities for Chinese transformation and renewal, deepens the understanding of traditional residential space succession theory arising from residential suburbanization, residential segregation, inner-city renewal, gentrification, and polarization of living space, enriches the case types of place identity theory in view of the unique value and function of the ECs, and provides a reference to carry out the renewal of old communities more successfully.